KONSEP MAS'ULIYAH DALAM ETIKA BISNIS ISLAM TERHADAP PERILAKU KONSUMSI KONTEN HIBURAN DIGITAL NETFLIX ( STUDI KASUS PADA MAHASISWA DI UNIVERSITAS HASYIM ASY’ARI ) - Dwi Rangga Prasetyo; Ninik Azizah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Digital transformation has reshaped entertainment consumption patterns, with Netflix emerging as the primary platform for millennial students. However, the growing consumption of digital content raises ethical dilemmas related to moral values and religiosity. This study examines the implementation of the Islamic principle of mas'uliyah (accountability) in students’ digital entertainment consumption behavior at Hasyim Asy'ari University. Employing a qualitative-descriptive and empirical juridical approach, data were collected through observation, in-depth interviews, documentation, and surveys involving 205 respondents across various faculties. Findings indicate a gap between ethical awareness and practice: while most respondents acknowledge the importance of responsibility in content selection, actual application remains low. Consumption tends to be driven by entertainment preferences rather than ethical considerations. This study recommends strengthening the internalization of mas'uliyah values through Islamic ethics-based education and digital literacy programs to promote more responsible and sustainable consumption patterns.